Determinan Pajak Penghasilan Badan Terutang Berdasarkan Biaya Operasional, Perencanaan Pajak dan Penjualan Bersih - Aliyani, Tunida; Machdar, Nera Marinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The largest source of state funding comes from taxes. This income tax is imposed on individuals and business entities that earn income will be taxed. The higher the income earned, the higher the tax burden will be. This study aims to examine in depth the factors that influence the amount of corporate income tax payable. This tax has a large contribution to tax revenue so that companies as the main contributors of income tax have an important role in state revenue. The method used is a descriptive approach using literature studies which are taken from journals and articles that are relevant to the research topic.